Effect of Nano Alumina on Compressive Strength and Microstructure of High Volume Slag and Slag-Fly Ash Blended Pastes - Shaikh, Faiz Uddin Ahmed; Hosan, Anwar (Frontiers in Materials, 2019)
This paper presents the effect of nano alumina (NA) on compressive strength and microstructure of cement paste containing high volume blast furnace slag (BFS) contents of 70%, 80% and 90% as partial replacement of cement and combined BFS and class F fly ash (FA) contents of 70% and 80% as partial replacement of cement. FA is used at 30% as partial replacement of BFS. NA contents are varied from 1% to 4% as partial replacement of BFS and BFS-FA. Results show that the addition of NA improves the compressive strength of high volume BFS and BFS-FA pastes by 2% to 16%. The compressive strength of paste containing 69% BFS, 30% cement and 1% NA exceeded the compressive strength of control cement paste while the compressive strength of paste containing 77% BFS, 20% cement and 3% NA is 1% lower than control cement paste. NA significantly reduced the large capillary pores of >0.1 microns of high volume BFS and BFS-FA pastes. No evidence of reduction of Ca(OH)2 in high volume BFS pastes is observed due to addition of NA, however, in high volume BFS-FA paste the Ca(OH)2 is reduced due to addition of NA. Increase in intensity peaks of CAH, Ettringite and CSH in X-ray diffraction analysis is observed in high volume BFS and BFS-FA pastes due to addition of NA, which coincides with the observed more dense microstructure of high volume BFS and BFS-FA pastes containing NA than those without NA.